Penerapan Air Rebusan Daun Kelor untuk Menurunkan Kadar Gula Darah pada Anggota Keluarga yang Mengalami Masalah Keperawatan Ketidakstabilan Kadar Glukosa Darah dengan Diagnosa Medis Diabetes Melitus di Wilayah Puskesmas Tarokan Kabupaten Kediri (Studi Kasus) - Asrori, Mohamad Bahrul; Prihananto, Dhian Ika; Risnasari, Norma (Lembaga Publikasi Ilmiah Nusantara, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by high blood sugar levels due to impaired insulin function. In addition to medical treatment, diabetes management can also utilize herbal therapies such as moringa leaves (Moringa oleifera), which are known to contain active ingredients that have the potential to lower blood glucose levels. This study aims to determine the effectiveness of boiled moringa leaf water in lowering blood sugar levels in family members experiencing nursing problems related to unstable blood glucose levels and a medical diagnosis of diabetes mellitus. The research method used was a descriptive case study with two respondents experiencing nursing problems related to unstable blood glucose levels of hyperglycemia. One glass of boiled moringa leaf water was given daily for four days. Blood sugar measurements before and after the intervention showed a significant decrease, with Mrs. T's blood sugar decreasing from 269 mg/dl to 213 mg/dl and Mrs. T's from 221 mg/dl to 165 mg/dl. These findings demonstrate that administering boiled moringa leaf water can be a safe and effective alternative complementary therapy to help control blood sugar levels in diabetic patients within the family.